Pengaruh Kompetensi Guru, Disiplin Kerja dan Kepuasan Kerja Terhadap Prestasi Kerja Guru SMK Di Kabupaten Magelang - Purwanto, Agung; Purbonuswanto, Welius (Media Manajemen Pendidikan, 2025)
This study aims to analyze the influence of teacher competence, work discipline, and job satisfaction on the job performance of Vocational High School (SMK) teachers in Salam and Mungkid Districts. The research method used is a quantitative method with a survey approach. Data were collected through questionnaires distributed to 150 SMK teachers in both districts. Data analysis was performed using multiple linear regression to determine the extent of the influence of each independent variable on the dependent variable. The results showed that teacher competence has a positive and significant effect on teacher job performance. Likewise, work discipline and job satisfaction also have a positive and significant impact on teacher job performance. Simultaneously, these three variables significantly contribute to improving teacher job performance. These findings indicate that to enhance teacher job performance, continuous efforts are needed to improve teacher competence through training and professional development, strengthen work discipline, and increase job satisfaction through incentives and a conducive work environment. This study provides practical implications for SMK administrators and educational policymakers in formulating strategies to improve teacher job performance. Additionally, this study contributes theoretically to enriching the literature on factors influencing teacher job performance, particularly in the context of vocational education in Indonesia. Keywords: Teacher Competence, Work Discipline, Job Satisfaction, Job Performance, SMK, Salam District, Mungkid District.